LEPRA PADA SISA RANGKA MANUSIA DARI LEWOLEBA: RELEVANSINYA TERHADAP SEJARAH PENGHUNIAN INDONESIA - Toetik Koesbardiati (Balai Arkeologi Yogyakarta, 2011)
Leprosy is a chronic, mildly communicable disease of man which primarily affects the skin, mucous membranes, peripheral nerves, eyes, bones and testes due to Mycobacterium leprae. Some researches show the evidence of leprosy spread worldwide in recent human history. Therefore, it is important to put leprosy’s case on the map to build broader knowledge, not only about the spread of leprosy, but also about human dispersal. The aim of the present study is to detect the M.leprae from ancient population in order to know its relevance to the peopling of Indonesia. Macroscopic method was performed based on Ortner method and Aufderheide and Rodriguez-Martin method to identify leprosy on the cranium of Lewoleba specimen (LLI/5), from Lembata Island, Indonesia. The antiquity of Lewoleba specimen is 2990+/-160BP. The results of the macroscopic method show that the specimen has suffered from leprosy in her lifetime. Some researchers concluded that emergence of leprosy related to human migration, in term of modern human dispersal, some researchers proved that the spread of leprosy worldwide consistent with the source of modern human (East Africa) and the spread of leprosy is also fit with the pattern of modern human dispersal. This fact provides an important clue how the M. leprae spread worldwide. Because the leprosy spread through human migration, this means also that leprosy could be infected the ancient people of Indonesia. This is because Indonesia was one of modern human migration’s route